Development of A 3D Tissue Slice Culture Model for the Study of Human Endometrial Repair and Regeneration - Muruganandan, Shanmugam; Fan, Xiujun; Dhal, Sabita; Nayak, Nihar R. (Biomolecules (Basel, Switzerland), 2020)
The human endometrium undergoes sequential phases of shedding of the upper functionalis zone during menstruation, followed by regeneration of the functionalis zone from the remaining basalis zone cells, and secretory differentiation under the influence of the ovarian steroid hormones estradiol (E2) and progesterone (P4). This massive tissue regeneration after menstruation is believed to arise from endometrial stromal and epithelial stem cells residing in the basal layer of the endometrium. Although many endometrial pathologies are thought to be associated with defects in these stem cells, studies on their identification and regulation are limited, primarily due to lack of easily accessible animal models, as these processes are unique to primates. Here we describe a robust new method to study endometrial regeneration and differentiation processes using human endometrial tissue slice cultures incorporating an air-liquid interface into a 3D matrix scaffold of type I collagen gel, allowing sustained tissue viability over three weeks. The 3D collagen gel-embedded endometrial tissue slices in a double-dish culture system responded to ovarian steroid hormones, mimicking the endometrial changes that occur in vivo during the menstrual cycle. These changes included the E2-induced upregulation of Ki-67, estrogen receptor (ER), and progesterone receptor (PR) in all endometrial compartments and were markedly suppressed by both P4 and E2 plus P4 treatments. There were also distinct changes in endometrial morphology after E2 and P4 treatments, including subnuclear vacuolation and luminal secretions in glands as well as decidualization of stromal cells, typical characteristics of a progestational endometrium in vivo. This long-term slice culture method provides a unique in vivo-like microenvironment for the study of human endometrial functions and remodeling during early pregnancy and experiments on stem cell populations involved in endometrial regeneration and remodeling. Furthermore, this model has the potential to enable studies on several endometrial diseases, including endometrial cancers and pregnancy complications associated with defects in endometrial remodeling.